Recession and Deflation? - David G. Blanchflower; Alex Bryson (Institute of Labor Economics (IZA), 2022)
Central bankers are raising interest rates on the assumption that wage-push inflation may lead to stagflation. This is not the case. Although unemployment is low, the labor market is not 'tight'. On the contrary, we show that what matters for wage growth are the non-employment rate and the under-employment rate. Both are high and act as brakes on wage growth. By lowering already low levels of consumer confidence, higher interest rates are liable to exacerbate workers' inability to maintain their real wages by reducing labor demand still further. Furthermore, we argue inflationary pressures have been generated by short-term supply side problems, rather than excessive demand in the economy. Under these conditions, just as in the Great Recession we anticipate deflation in the near future, coupled with rising joblessness and recession.
Keywords: E31; E43; J2; J3; J64; 330; unemployment; non-employment; wages; inflation; labor market